INTEGRATING INFORMATION & CYBER SECURITY INTO A LEARNING PROCESS PARTICIPANTS’ CURRICULUM - Bohatyrets, Valentyna; Banar, Evelina (Національний університет «Львівська політехніка», 2023)
Current security environment has dramatically changed from the one we’ve been engaged in for the last 30 years and it requires new ways of thinking and new ways of acting. In this regard, education, to be more precise, Higher Education Institutions (HEIs) have always been a core pillar of promoting a society’s sustainable development through knowledge-drive actions; since at the times of global turmoil and russia’s war against Ukraine, education involves every aspect of human life: culture, information, cybersecurity and media literacy, power, ideology, and authorities’ impact. Consequently, the objective of HEIs is to update and modernize education system by integrating various courses into curricula and, respectfully, developing effectively impactful programs, employing evidence-based solutions, to achieve this goal, the educational process must include the peculiarities of the sustainable development of a modern society, which is characterized by the multiplicity of languages, cultures, and texts circulating in the information space created by modern means of mass communication.
Keywords: Higher Education Institutions (HEIs); curriculum; information society; information and cyber security courses; media literacy; IT and network architecture; Dept. of International Relations and Public Communications